1978
DOI: 10.1136/oem.35.4.292
|View full text |Cite
|
Sign up to set email alerts
|

TruCutR needle biopsy in asbestosis and silicosis: correlation of histological changes with radiographic changes and pulmonary function in 41 patients.

Abstract: A percutaneous needle biopsy was performed with a TruCutR needle on 41 patients with suspected pneumoconiosis. Patients selected for biopsy tended to have brief or unusual dust exposure, as well as questionable radiographic opacities. Sixteen had been exposed to asbestos, 13 to silica and 12 to mixed dust containing quartz, coal, iron, asbestos and talc. All patients in the asbestos group and most in the other two groups had a reduced transfer factor. Most patients in the asbestos group and about 25 % of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
1993
1993

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In asbestosis, animal studies indicate that the asbestos fibers are first deposited on the alveolar ducts and subsequently are phagocytized by alveolar macrophages and type II epithelial cells. 7,[29][30][31] Following phagocytosis of asbestos, in vitro studies have demonstrated that alveolar macrophages release reactive oxygen species, 32,33 proteolytic enzymes; chemotactic factors, including leukotrienes, 34 neutrophil chemotactic factor; 35,36 cytokines, including tumor necrosis factor; 37 and fibronectin. 32 These products can cause direct damage to the alveolar epithelium and interstitium and may also attract other inflammatory cells, including neutrophils, lymphocytes, and eosinophils into the alveolar compartment.…”
Section: Cellular Measures Of Lung Injurymentioning
confidence: 99%
“…In asbestosis, animal studies indicate that the asbestos fibers are first deposited on the alveolar ducts and subsequently are phagocytized by alveolar macrophages and type II epithelial cells. 7,[29][30][31] Following phagocytosis of asbestos, in vitro studies have demonstrated that alveolar macrophages release reactive oxygen species, 32,33 proteolytic enzymes; chemotactic factors, including leukotrienes, 34 neutrophil chemotactic factor; 35,36 cytokines, including tumor necrosis factor; 37 and fibronectin. 32 These products can cause direct damage to the alveolar epithelium and interstitium and may also attract other inflammatory cells, including neutrophils, lymphocytes, and eosinophils into the alveolar compartment.…”
Section: Cellular Measures Of Lung Injurymentioning
confidence: 99%